Risiko Pengelolaan Dana Desa dan SILPA dalam Perspektif Akuntabilitas Publik Kecamatan Tugumulyo Musi Rawas - Okpriyanto, Deni; Leniwati, Driana; Malik, Nazaruddin (Akuntansi & Ekonomika, 2026)
This study aims to analyze the risks in village fund management that contribute to the high occurrence of Budget Surplus (SILPA) from the perspective of public accountability. This research employs a qualitative exploratory approach conducted in Tugumulyo District, Musi Rawas Regency. Data were collected through interviews, observation, and documentation. The results reveal that high SILPA is influenced by limited human resource capacity, bureaucratic fear of legal risks, and weak risk-based planning. These conditions lead to delayed public services and declining public trust. Strengthening risk management and improving governance are essential to achieve Good Village Governance.